2018
DOI: 10.14710/jpki.13.2.168-178
|View full text |Cite
|
Sign up to set email alerts
|

Karakteristik Ibu dan Faktor Risiko Kejadian Kematian Bayi di Kabupaten Banjarnegara

Abstract: Latar Belakang: Kabupaten Banjarnegara pada tahun 2012 menjadi Kabupaten dengan angka kematian bayi (AKB) tertinggi di Provinsi Jawa tengah. Dalam lima tahun terakhir angka kematian bayi sudah mengalami penurunan namun belum signifikan. Tujuan penelitian ini adalah untuk menganalisis karakteristik ibu dan beberapa faktor risiko yang berhubungan dengan kejadian kematian bayi di kabupaten Banjarnegara. Metode: Penelitian ini merupakan penelitian survei dengan pendekatan kasus kontrol dengan jumlah kelompok kasus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
5
0
4
Order By: Relevance
“…However, these results are inversely proportional to the research conducted by Kusumawardani and Handayani (2018). In the research, it was stated that between the age of the mother with the incidence of death in infants there was no significant relationship.…”
Section: Discussionmentioning
confidence: 91%
“…However, these results are inversely proportional to the research conducted by Kusumawardani and Handayani (2018). In the research, it was stated that between the age of the mother with the incidence of death in infants there was no significant relationship.…”
Section: Discussionmentioning
confidence: 91%
“…AKI merupakan rasio kematian ibu yang terjadi dan/disebabkan pada masa kehamilan, persalinan, dan nifas (Wijayanti et al, 2019). Sedangkan pada Angka Kematian Bayi (AKB) per 1000 kelahiran hidup bayi meninggal usia 0 tahun sampai sebelum mencapai usia satu tahun (Kusumawardani & Handayani, 2018).…”
Section: Pendahuluanunclassified
“…The birth weight and length of the baby is an indicator of the status of the baby's growth and development. The problem of the size of the baby, both the weight and length of the baby is an assessment that can be seen since the mother carried out an antenatal examination with an abdominal examination and anamnesis related to the nutritional status and health of the mother (Kusumawardani & Handayani, 2018). Other anthropometric examinations that were examined were head circumference and chest circumference, from the examination the baby Mrs. M has a head circumference of 34 cm and a chest circumference of 32 cm, the results of the examination showed that the baby Mrs. M is normal because according to the theory that the head circumference and chest circumference of a normal newborn are 33-35 cm, and 30-38 cm.…”
Section: Newbornmentioning
confidence: 99%
“…One of the efforts that can be done to reduce MMR is suggested that health workers are expected to prevent obstetric and neonatal complications, such as asphyxia, congenital abnormalities, other co-morbidities in infants and hypertension in pregnancy and the puerperium. When pregnant women are monitored closely, namely by conducting timely and complete Antenatal Care (ANC) for pregnant women including giving Fe (iron) tablets to mothers and monitoring them through maternal and child health surveillance officers (Kusumawardani & Handayani, 2018).…”
Section: Introductionmentioning
confidence: 99%